(untitled) (Raparin Journal of Humanities (RJH), 2024)
One of the most important subjects that have been talked about it is “Education & Teaching” especially for now a day is a living subject. During the raise of education it has been always a subject that Muslim community concern about it. Education is a real service for humanity in the future. Education regards as a differentiation between the communities. We can say it shows how human being will act and behave around. Of course with the appearance of human being education was existed. So that most of the scientist in different nations they talk about it. Among Kurdish people there is also scientist who gave important to it. Melay Gewra is one of them. He was a role model in his time that he could give a great influence in a wearing his community in different genre especially Islamic education، Social Teaching، awareness، Politics...etc No doubt Mela Gewre hadn’t wrote any book about education meanwhile in a time of reading his book the reader will realize the thought and ideas about the education. His books talk about the social problems in his community. One of his Golden speeches about the teaching of education is: Teachers should be trainers in his area especially the religious men. They have to try and grow up in most of the parts not only in religion parts because the society needs to be renewed and grow up to fit the time century. That’s why Melay Gewre think that understanding of the education as itself and practicing it brings services to the human being’s community in this world and after this world، vise verse، the misunderstanding of education it brings distraction of science that end up with the ignorance of the community.